2013
DOI: 10.1039/c3cc42424c
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable NHC-promoted ring-opening polymerizations

Abstract: The UV-induced photocyclization of a dithienylethene-annulated N-heterocyclic carbene precatalyst enabled photoswitchable ring-opening polymerizations of ε-caprolactone and δ-valerolactone. The polymerizations proceeded efficiently in ambient light, however UV irradiation attenuated the reaction rate (k(amb)/k(UV) = 59). Subsequent visible light exposure reversed the photocyclization and restored catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
104
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 31 publications
2
104
0
1
Order By: Relevance
“…Although a variety of stimuli can be a priori envisioned for switchable catalysts, mostly redox chemo‐switchable metal catalysts2429 have been described for the ROP of cyclic esters, although one example of allosteric control by non‐redox chemical switching of a metal‐based catalyst has also been reported 30. Moreover, some examples using chemo‐switchable31 and photo‐switchable32 organocatalysts have recently appeared, the concept and modus operandi of which can, in principle, be extended to metal‐based catalysts. Hence, all of these different switchable ROP systems are described hereafter.…”
Section: Switchable Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although a variety of stimuli can be a priori envisioned for switchable catalysts, mostly redox chemo‐switchable metal catalysts2429 have been described for the ROP of cyclic esters, although one example of allosteric control by non‐redox chemical switching of a metal‐based catalyst has also been reported 30. Moreover, some examples using chemo‐switchable31 and photo‐switchable32 organocatalysts have recently appeared, the concept and modus operandi of which can, in principle, be extended to metal‐based catalysts. Hence, all of these different switchable ROP systems are described hereafter.…”
Section: Switchable Catalysismentioning
confidence: 99%
“…However, the use of photochemical switches remains essentially unexplored in cyclic ester ROP catalysis. To our knowledge, there is no such example with a metal‐based ROP catalyst and the only report consists in a photoswitchable organocatalyst reported by Neilson and Bielawski in 2013 32…”
Section: Switchable Catalysismentioning
confidence: 99%
“…[1] An attractive class of substrates for incorporating lightresponsive groups are the N-heterocyclic carbenes (NHCs) as they have been used in ab road range of organometallic and organocatalysts. [7] Similarly,aRh catalyst bearing the same NHC was found to catalyze hydroborations. [3] We recently developed ap hotoswitchable NHC by incorporating ap hotochromic [4] dithienylethene (DTE) [5] unit into an imidazolylidene backbone,and found that the corresponding carbene functioned as ap hotoswitchable organocatalyst for transesterification and transamidation [6] reactions as well as for ring-opening polymerizations.…”
mentioning
confidence: 99%
“…Recent developments have focused on the latent ROP of cyclic esters to yield the desired polyesters, the majority of the examples again based on NHCs. Bielawski and Neilson presented a UV‐switchable NHC, where a change of light source induced a cyclization or opening of the NHC backbone . This results in a considerable change of electron density at the carbene center, rendering imidazolium derivative 15 active for the ROP of δ ‐valeroclactone and ε‐caprolactone in the presence of benzylic alcohol as co‐initiator, while derivative 16 is strongly deactivated ( k 15 / k 16 = 59, Scheme ).…”
Section: Polyestersmentioning
confidence: 99%
“…Preparation of a polyester by a photoswitchable NHC. UV irradiation entails formation of a large conjugated system, rendering 16 almost inactive …”
Section: Polyestersmentioning
confidence: 99%